Pyoderma gangrenosum with splenic abscess- A rare association - Aditi Bansal; Ankur Singla; Aminder Singh; Sukhjot Kaur (Wolters Kluwer Medknow Publications, 2022)
Pyoderma gangrenosum is a rare, chronic neutrophilic dermatosis of unknown etiology. The classical clinical feature of pyoderma gangrenosum is a pustule or plaque that rapidly progresses to a painful, necrotic ulcer with undermined violaceous margins. Pyoderma gangrenosum may be associated with underlying inflammatory bowel diseases, hematological malignancies, or rheumatologic disorders in 50-70% of the cases. The visceral involvement by pyoderma gangrenosum is rare. Sterile neutrophilic infiltrates in organs other than the skin are uncommon systemic manifestations of neutrophilic dermatoses, but have occasionally been reported. We report a case of a 38-year-old female with pyoderma gangrenosum and visceral involvement manifesting as splenic abscess.